PENERAPAN STRATEGI PEMBELAJARAN INKUIRI JURISPRUDENSIAL DALAM UPAYA MENINGKATKAN KETERAMPILAN BERBICARA SISWA PADA PELAJARAN BAHASA INDONESIA - Putu Dessy Fridayanthi (Widyadari : Jurnal Pendidikan, 2022)
Jurisprudential inquiry strategy is a learning strategy that aims to teach students to analyze and think systematically and critically on issues that are currently hot in society. The objectives of this study are (1) to describe and explain the application of jurisprudential inquiry learning strategies for learning students' speaking skills, (2) to increase student activity in the speaking learning process through the application of jurisprudential inquiry learning strategies to students, and (3) to improve students' speaking skills. students through jurisprudential inquiry learning strategies to students. This type of research is action research. The subjects of this action research are students of class XI MIPA 2 SMA Negeri 7 Denpasar in the 2021/2022 academic year. Techniques used to collect data include observation, document review interviews, questionnaires, and tests. This study used three cycles, and each cycle went through four stages of the activity process (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. The data collection technique in this research is using the test and observation method. The results showed (1) Jurisprudential inquiry learning strategies can be applied to students' speaking skills, (2) Jurisprudential inquiry learning strategies can increase students' activeness in the speaking learning process in students' classes, (3) Jurisprudential inquiry learning strategies can improve students' speaking skills.